A REVIEW PAPER ON OFFLINE INSPECTION OF FINISHED AND SEMI-FINISHED PRODUCTS AND EMERGING RESEARCH DIRECTIONS - RAMZAN, Muhammad BABAR; KANG, Chang WOOK; SARKAR, Biswajit (Yugoslav Journal of Operations Research, 2016)
Organizations wants to focus on product quality along with productivity to get their competitive advantage in global market. In order to achieve this aim, quality management system and its different aspects are becoming more valuable than before. This study has considered quality control and its activities with specific focus on offline inspection. The objective of this study is to provide a literature review that identifies different models and methodologies, developed for offline inspection under different manufacturing and inspection conditions. This review is based on research work accepted by international journals and published in the years from 2000 to 2016.These studies are classified into six groups on the basis of their research objectives, model developed, adopted methodologies, and research outcomes. This review paper also gives а brief look at the offline inspection to propose future research opportunities and emerging trends. The proposed research directions can be helpful in developing new models or modifying the existing models to improve the performance of offline inspection.